PELAKSANAAN OTONOMI DAERAH DAN DAMPAKNYA TERHADAP PEMBANGUNAN MASYARAKAT DI KABUPATEN INDRAGIRI HILIR - Iqbal, Muhammad; Herman, Herman (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2018)
This study , entitled " Implementation of the Regions autonomi and Its Impact on Community Development in Indragiri Hilir " . The purpose of this study is to investigate the implementation of regional autonomy and its influence on development in Indragiri Hilir . Granting regional autonomy does not run properly categorized in Indragiri Hilir district. In addition , the effect on the implementation of community development are not well categorized on the development of basic facilities , infrastructure as well as the multi-year development . From the research framework of systems theory analysis showed that the Government Development Indragiri Hilir the category is not well (out come ) with law No. 23 of 2014.